GROWTH RESPONSE OF ROBUSTA COFFEE (Coffea robusta L.) GROWTH ON CHICKEN CAGE FERTILIZER AND FERTILIZER LIQUID ORGANIC - Ahmad Ridwan Lubis (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
The purpose of this research is to know the response of robustacoffee seedling from the application of chicken manure and liquid organic fertilize. This research was held in land that are on Kecamatan Medan Johor road, North Sumatra with altitude ±32 meters above the sea level, started from May until September 2016. This research was using factorial randomized block design with 2 factors. The first factor is the application of chicken manure (topsoil:manure)with four levels, namely: (1:0); (3:1); (2:1); (1:1) and the application of liquid organic fertilizer with four levels of 0 cc/l; 2 cc/l; 4 cc/l; 6 cc/l. The observed parameters were plant height (cm), stem diameter (mm), root volume (cm3), totalleaf area (cm2), dry weight of root (g), dry weight of shoot (g), and shoot-root ratio. The result showed that chicken manure treatment significantly increased the plant height, stem diameter, root volume, total leaf area, dry weight of root, dry weight of root and shoot-root ratio. The application of liquid organic fertilizer significantly increased the total leaf area parameter. The interaction between both treatments significantly increased dry weight of root, dry weight of shoot and total leaf area parameters.